Impact of soil and water conservation measures on farm productivity and income in the semi-arid tropics of Bundelkhand, central India. (22nd December 2022) - Choudhary, Bishwa Bhaskar; Dev, Inder; Singh, Priyanka; Singh, Ramesh; Sharma, Purushottam; Chand, Khem; Garg, Kaushal K; Anantha, KH; Akuraju, Venkataradha; Dixit, Sreenath; Kumar, Sunil; Ram, Asha; et al.
Summary: Soil and water are crucial resources for agriculture, especially in arid and semi-arid rain-fed areas, yet farm-level economic impacts and the factors influencing the adoption of measures for their conservation are little studied. The present study used data from 400 farm households to assess factors influencing the adoption of soil and water conservation measures (SWCMs) and their impacts on farm productivity and income in a semi-arid region of central India. We employed a probit model to determine the factors influencing the on-farm adoption of SWCMs and a propensity score matching technique for assessing their impacts. The findings indicate that farmer age and education, off-farm income, farm size and land ownership and access to training are key drivers of the adoption of SWCMs. SWCMs accentuated the input costs by INR 1689–2847 per ha during the rabi cropping season (October–February), but also increased crop productivity and net revenue from farming. The impact in the rabi season was less sensitive to the unobserved confounders than in the kharif season (June–September). Therefore, SWCMs could represent an important strategy for unlocking the cultivation potential of large rain-fed areas and for sustaining the livelihoods of farm households in the ecologically fragile arid and semi-arid tropics.